1842 Ohio Acts 73, An Act to Incorporate the Woodland Cemetery Association of Dayton, § 5 (vol. 40) - (:unkn) unknown (My University, 1841)
That any person who shall willfully . . . shoot or discharge any gun within the limits aforesaid, shall be deemed guilty of a misdemeanor
Keywords: DISCHARGE